2010
DOI: 10.1155/2010/716473
|View full text |Cite
|
Sign up to set email alerts
|

FTIR imaging and ATR-FT-Far-IR synchrotron spectroscopy of pig ear skin

Abstract: FTIR imaging was performed on pig ear skin samples cryo-sectioned perpendicular to the skin surface. The OH-stretch region revealed the distribution of water; the amide II band gave the protein distribution; the C═O stretch and C–H stretch regions showed the variation in lipids. Water and proteins were similarly distributed. Triglycerides were predominantly found in the deeper skin layers whereas free fatty acids and ceramides were more dominant in the upper layers. ATR-FT-Far-IR spectroscopy with synchrotron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Previous studies of skin tissue and percutaneous penetration by imaging techniques include confocal laser scanning microscopy (CLSM), , infrared (IR) imaging, Raman imaging, and various imaging techniques based on mass spectrometry, such as matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) , and time-of-flight secondary ion mass spectrometry (TOF-SIMS) . These studies have mainly focused on the characterization of skin constituents ,,, or the penetration of fluorescent molecules, , nonactive ingredients (e.g., solvents), surfactants, or penetration enhancers. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of skin tissue and percutaneous penetration by imaging techniques include confocal laser scanning microscopy (CLSM), , infrared (IR) imaging, Raman imaging, and various imaging techniques based on mass spectrometry, such as matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) , and time-of-flight secondary ion mass spectrometry (TOF-SIMS) . These studies have mainly focused on the characterization of skin constituents ,,, or the penetration of fluorescent molecules, , nonactive ingredients (e.g., solvents), surfactants, or penetration enhancers. , …”
mentioning
confidence: 99%
“…Previous studies of skin tissue and percutaneous penetration by imaging techniques include confocal laser scanning microscopy (CLSM), 8,9 infrared (IR) imaging, 10−13 Raman imaging, 14−16 spectrometry, such as matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) 17,18 and timeof-flight secondary ion mass spectrometry (TOF-SIMS). 19 These studies have mainly focused on the characterization of skin constituents 10,11,15,18 or the penetration of fluorescent molecules, 8,9 nonactive ingredients (e.g., solvents 12 ), surfactants, 14 or penetration enhancers. 13,16 Compared to other imaging techniques, mass spectrometry has the advantage of high chemical specificity without requiring the use of labels, such as isotopes or fluorescent tags, thereby ensuring the analysis of the parent molecule and not a combination of the parent molecule and metabolites containing the isotope or tag.…”
mentioning
confidence: 99%
“…In the HHS experimental spectrum we do observe several small-amplitude oscillations at approximately 105 cm −1 , 120 cm −1 , 135 cm −1 , 140 cm −1 , 150 cm −1 , and 158 cm −1 . The smaller amplitude modes in HHS spectrum most likely represent small-scale internal fluctuations that have been observed in previous THz studies [ 54 ]-–[ 56 ] on globular proteins and other peptides.…”
Section: Resultsmentioning
confidence: 61%
“…In addition to lotion sunscreens, other products that contain UV blocking or absorbing active ingredients, such as lip balms, insect repellents, and tinted moisturizers, can be analyzed using this method. Students can analyze antioxidants such as vitamin C in the sunscreens, because previous research has suggested they may have a major effect on skin protection. ,,, To ensure the pig skin has sunscreen before UV irradiation, infrared spectroscopy using a diffuse reflectance infrared Fourier transform (DRIFT) or attenuated total reflectance (ATR) accessory can be used to confirm the presence of functional groups by comparing a spectrum of the sunscreen obtained using ATR to the spectrum of a treated pig skin disk obtained using ATR or DRIFT. Students can also extract the melanin from the pig skin and use a standard curve to quantify it. This would enable students to normalize the radical signal on the basis of melanin .…”
Section: Resultsmentioning
confidence: 99%